Increased serum activin A level in congenital heart disease‐associated pulmonary artery hypertension: A comparative study from the COHARD‐PH registry - Muhammad R. Hadwiono; Anggoro B. Hartopo; Widya Wasityastuti; Dyah W. Anggrahini; Gusty R. T. Ryanto; Noriaki Emoto; Lucia K. Dinarti (Pulmonary Circulation, 2023)
Abstract Activin A, a member of TGF‐β superfamily, has been implicated in the pathogenesis of pulmonary artery hypertension (PAH). PAH due to congenital heart disease (CHD‐PAH) is a major problem in developing countries. Activin A may have a role in PAH development and progression among uncorrected CHD. In this comparative study, serum activin A level was significantly increased in subjects with uncorrected CHD without the presence of PH and were more significantly risen in CHD‐PAH, as compared to control. The utilization of serum activin A measurement seems promising to identify uncorrected CHD patients with PAH development and progression.